EFL Teachers’ Perceptions on Supervision Program as a Tool to Develop Teachers’ Professionalism - Tosriadi Tosriadi; Abdul Asib; Sri Marmanto (AT-TA'LIM, 2018)
Teachers hold a very crucial role in education. Students’ success in academic life is very much influenced by teachers’ quality. One of the ways applied by most schools in Indonesia to assure their teachers quality is by conducting supervision program at the end or in the middle of semester. This study investigated teachers’ perception on the effectiveness of supervision program in relation to their professional development. This qualitative case study involved 4 EFL teachers teaching at various school levels; elementary school, junior high school and senior high school. The data were collected through interview and document analysis. The result of data analysis revealed that teachers hold positive attitude toward supervision program in helping them develop their professionalism in teaching. Schools need to maintain supervision program to make sure their teachers are well prepared in performing their duty. The participating teachers suggested for its meaningfulness, supervision program should be well designed. Teachers being observed and supervisor should have the same educational background.